Radiotherapy for benign calcaneodynia: long-term results of the Erlangen Dose Optimization (EDO) trial - Ott, Oliver J.; Jeremias, Carolin; Gaipl, Udo; Frey, Benjamin; Schmidt, Manfred; Fietkau, Rainer (Strahlentherapie und Onkologie, 2014)
The goal of this work was to evaluate the long-term efficacy of two dose-fractionation schedules for radiotherapy of calcaneodynia.Between February 2006 and February 2010, 457 evaluable patients were recruited for this prospective trial. All patients received orthovoltage radiotherapy. One course consisted of 6 fractions/3 weeks. In case of insufficient remission of pain after 6 weeks a second series was performed. Patients were randomly assigned to receive either single doses of 0.5 or 1.0 Gy. Endpoint was pain reduction. Pain was measured before, right after (early response), 6 weeks (delayed response), and approximately 2.5 years after radiotherapy (long-term response) with a questionnaire-based visual analogue scale (VAS) and a comprehensive pain score (CPS).The median follow-up was 32 months (range 9-57 months). The overall early, delayed, and long-term response rates for all patients were 87, 88, and 95%. The mean VAS values before treatment, for early, delayed, and long-term response for the 0.5 and 1.0 Gy groups were 65.5 ± 22.1 and 64.0 ± 20.5 (p = 0.19), 34.8 ± 24.7 and 39.0 ± 26.3 (p = 0.12), 25.1 ± 26.8 and 28.9 ± 26.8 (p = 0.16), and 16.3 ± 24.3 and 14.1 ± 19.7 (p = 0.68). The mean CPS values before treatment, for early, delayed, and log-term response were 10.1 ± 2.7 and 10.0 ± 3.0 (p = 0.78), 5.6 ± 3.7 and 6.0 ± 3.9 (p = 0.34), 4.0 ± 4.1 and 4.3 ± 3.6 (p = 0.26), and 2.1 ± 3.3 and 2.3 ± 3.2 (p = 0.34), respectively. No significant differences in long-term response quality between the two arms were found (p = 0.50).Radiotherapy is a very effective treatment for the management of benign calcaneodynia. For radiation protection reasons, the dose for a RT series should not exceed 3.0 Gy.
EVALuna2:18187